REMOTE Ischemic Perconditioning Among Acute Ischemic Stroke Patients in Catalonia: REMOTE-CAT PROJECT - Purroy, Francisco; Arque, Gloria; Mauri, Gerard; García-Vázquez, Cristina; Vicente-Pascual, Mikel; Pereira, Cristina; Vazquez-Justes, Daniel; Torres-Querol, Coral; Vena, Ana; Abilleira, Sònia; Cardona, Pere; Forné, Carles; et al. (Frontiers in Neurology, 2020)
Rationale Remote ischemic perconditioning during cerebral ischemia (RIPerC) refers to the application of brief episodes of transient limb ischemia commonly to a limb, it represents a new safe, simple and low-cost paradigm in neuroprotection. Aim and/or hypothesis To evaluate the effects of RIPerC on acute ischemic stroke (AIS) patients, applied in the ambulance, to improve functional outcomes compared with standard of care. Sample size estimates A sample size of 286 patients in each arm achieves 80% power to detect treatment differences of 14% in the outcome, using a two-sided binomial test at significance level of 0.05, assuming that 40% of the control patients will experience good outcome and an initial misdiagnosis rate of 29%. Methods and design We aim to conduct a multicentre study of pre-hospital RIPerC application in AIS patients. A total of 572 adult patients diagnosed of suspected clinical stroke within 8 hours of symptom onset and clinical deficit >0 according to prehospital rapid arterial occlusion evaluation (RACE) scale score will be randomized, in blocks of size 4, to RIPerC or sham. Patients will be stratified by RACE score scale. RIPerC will be started in the ambulance before hospital admission and continued in the hospital if necessary. It will consist of five cycles of electronic tourniquet inflation and deflation (5 min each). The cuff pressure for RIPerC will be 200 mmHg during inflation. Sham will only simulate vibration of the device. Study outcome(s) The primary outcome will be the difference in the proportion of patients with good outcomes as defined by a mRS score of 2 or less at 90 days. Secondary outcomes to be monitored will include early neurological improvement rate, treatment related serious adverse event rates, size of the infarct volume, symptomatic intracranial haemorrhage, metabolomic and lipidomic response to RIPerC and Neuropsychological evaluation at 90 days. Discussion Neuroprotective therapies could not only increase the benefits of available reperfusion therapies among AIS patients but also provide an option for patients who are not candidates for these treatments. REMOTE-CAT will investigate the clinical benefit of RIC as a new neuroprotective strategy in AIS. Clinicaltrials.gov number: NCT03375762.